Caracterização histoquímica e imuno-histoquímica das alterações fibróticas nas endometroses das éguas - Costa, Leonardo Dourado da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Endometrosis is a degenerative change of the uterine glands and surrounding stroma, characterized by periglandular arrangement of myofibroblasts and deposition of extracellular matrix (ECM). The aim of this study was evaluate the expression of collagen type I, III and IV and α-smooth muscle actin (α-SMA) in equine endometroses, and investigate the role of myofibroblasts in the progression of these processes. A parallel was made with histochemical techniques of Masson's trichrome, Picrosirius Red under polarized light and Periodic Acid-Schiff (PAS). Twenty four uterine biopsies received by the Veterinary Pathology Service and Animal Reproduction of FMVZ, UNESP, Botucatu, SP, were diagnosed with endometrosis. Histological analysis revealed that the orange dense collagen fibers correspond to type I collagen, being prevalent in inactive and inactive destructive endometrosis. And the green loose collagen fibers correspond to type III collagen, and are predominant in active and active destructive endometrosis. In the same processes, a greater amount of periglandular myofibroblasts were observed in comparison to inactive and inactive destructive endometrosis. The presence of these cells in active processes are strongly related to an increased deposition of collagen type III in fibrotic nests. Regarding the basement membrane, the active destructive and active endometrosis shows thickening, apparently not related to an increase in expression of type IV collagen. The active destructive and inactive destructive endometrosis exhibited disruption areas in type IV collagen fibers. Thus, it is noted that the myofibroblasts are related to increased deposition of type III collagen in active fibrotic nests

A endometrose é uma alteração degenerativa das glândulas uterinas e do estroma circundante, caracterizada pelo arranjo periglandular de miofibroblastos e a deposição de matriz extracelular (ECM). O presente trabalho objetivou avaliar a expressão de colágeno tipo I, III e IV e α-actina de músculo liso (α-SMA) nas endometroses equinas, procurando esclarecer a participação dos miofibroblastos na progressão destes processos. Foram utilizadas 24 biópsias uterinas com diagnóstico de endometrose, recebidas pelo Serviço de Patologia Veterinária e de Reprodução Animal da FMVZ, UNESP, Botucatu, SP. Cortes histológicos foram submetidos às técnicas histoquímicas de Tricrômico de Masson, Picrosirius Red sob luz polarizada e Ácido Periódico de Schiff (PAS) e imuno-histoquímicas para os três tipos de colágeno citados e α-SMA. Ainda, traçou-se um paralelo entre a técnica de Picrosirius Red e a imunomarcação dos colágenos tipos I e III. A análise histológica revelou que as fibras de colágeno denso correspondem ao colágeno tipo I, predominantes nas endometroses inativa e inativa destrutiva. As fibras de colágeno frouxo correspondem ao colágeno tipo III, predominantes nas endometroses ativas e ativas destrutivas. Nestes mesmos processos, a membrana basal revelou espessamento, aparentemente não relacionado ao colágeno tipo IV, e uma maior imunomarcação de miofibroblastos periglandulares em relação às endometroses inativa e inativa destrutiva. Desta forma, nota-se que os miofibroblastos estão relacionados ao aumento na deposição de colágeno tipo III nos ninhos fibróticos ativos
Histochemical and immunohistochemical characterization of fibrotic changes in mares endometrosis
Keywords: Imuno-histoquímica; Endometrose; Miofibroblastos; Egua - Doenças; Fibroblasto; Colageno; Infecundidade em animais; Myofibroblasts